Morphological and Molecular Characterization of a New Root-Knot Nematode, Meloidogyne limonae n. sp. (Nematoda Meloidogynidae), Parasitizing Lemon in China - Sun, Yangfang (Plant disease, 2024)
Root-knot nematodes of the genus Meloidogyne parasitize the roots of thousands of plants and can cause severe damage and yield losses. Here, we report a new root-knot nematode, Meloidogyne limonae n. sp., parasitizing "lemon" (Citrus limon) in Hainan Province, South China. Lemon trees infected by the root-knot nematode showed poor-quality lemons, chlorosis of foliage, weak growth, and numerous root galls with white females and egg masses protruding outside. Phylogenetic trees of sequences within the ribosomal and mitochondrial DNA demonstrated that this species differs clearly from other previously described root-knot nematodes. Morphologically, the new species is characterized by an oval-shaped perineal pattern and the lateral field marked by a ridge of cuticle on one or both sides; the dorsal arch is low, with fine to coarse, smooth cuticle striae; the vulva slit is centrally located at the unstriated area; the spicules of males are arcuate and curved ventrally; the gubernaculum is distinct and curved; the labial disc of second-stage juveniles is prominent and dumbbell shaped; stylet knobs are oval and sloping backwardly; pharyngeal glands are not filling the body cavity and overlapping the intestine ventrally; and the conical tail is gradually tapering. Phylogenetic trees based on the ITS1-5.8S-ITS2, D2-D3 of the 28S rDNA, and COI and COII-16S rRNA genes of the mtDNA showed that M. limonae n. sp. belongs to an undescribed root-knot nematode lineage that is separated from other species with the resemblance in morphology, such as M. floridensis, M. hispanica, M. acronea, and M. paranaensis